2003
DOI: 10.1152/jn.00779.2002
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Anticipation of Different Task Dynamics: Rapid Recall of Appropriate Motor Skills Using Visual Cues

Abstract: Recent studies have reported that human subjects show varying degrees of ability to use contextual cues to recall the motor skills required to compensate for different dynamic external force fields during arm movements. In particular, the subjects showed little or no ability to use color cues to adjust motor outputs in anticipation of the perturbing fields after limited periods of training that were sufficient to learn to compensate for the fields themselves. This is unexpected since humans and monkeys can use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 18 publications
3
58
0
Order By: Relevance
“…Also, during associative learning, there were reports of firing rate changes in this area (although not representing the task parameters) (Mitz et al, 1991). Furthermore, there is agreement with psychophysical studies showing that the motor system can use contextual information (for example, for rapid task switching) (Krouchev and Kalaska, 2003;Wada et al, 2003;Mistry and Contreras-Vidal, 2004).…”
Section: Learning-related Responsessupporting
confidence: 56%
“…Also, during associative learning, there were reports of firing rate changes in this area (although not representing the task parameters) (Mitz et al, 1991). Furthermore, there is agreement with psychophysical studies showing that the motor system can use contextual information (for example, for rapid task switching) (Krouchev and Kalaska, 2003;Wada et al, 2003;Mistry and Contreras-Vidal, 2004).…”
Section: Learning-related Responsessupporting
confidence: 56%
“…Our results support the idea that force field learning is akin to learning to manipulate an object and, accordingly, only (visual) contextual cues that associated the force field with an object guarded against interference. Strikingly, these visual cues conferred a benefit on subjects even without extensive training and without associating the force and null fields with different arm postures, effectors, or motor tasks (Conditt et al 1997;Gandolfo et al 1996;Hwang et al 2006;Krouchev and Kalaska 2003;Shadmehr and Mussa-Ivaldi 1994;Tong et al 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Without informative contextual cues, it is conceivable that previously learned motor behavior persists, leading to errors when a new task requires a change in motor behavior (Conditt et al 1997;Gandolfo et al 1996;Goodbody and Wolpert 1998;Malfait et al 2005;Mattar and Ostry 2007;Shadmehr and Moussavi 2000;Shadmehr and Mussa-Ivaldi 1994;Tong et al 2002). The search for cues that reduce interference in force field learning has yielded mixed findings (Gandolfo et al 1996;Krouchev and Kalaska 2003;Osu et al 2004;Wada et al 2003). Building on recent studies that have suggested that force field learning is akin to learning to manipulate a novel object (Cothros et al 2006b;Kluzik et al 2008;Lackner and DiZio 2005), this study considers more focused cues, specifically visual cues that relate to object grasp.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been demonstrated that subjects can learn opposing force fields if the posture of the arm is altered between the two fields (Gandolfo et al, 1996). However, arbitrary sensory cues, such as color or changes in proprioceptive information from joints not involved in the movement task, are not effective contextual cues promoting independent learning of opposing force fields applied in alternation (Gandolfo et al, 1996;Seidler et al, 2001;Krouchev and Kalaska, 2003;Osu et al, 2004). Here, we tested whether functional (and nonarbitrary) changes in sensory feedback, namely changes in cutaneous feedback when applying loads to the hand versus arm segments, can facilitate independent learning of opposing dynamic tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have sought to determine whether opposing tasks can be represented independently in memory by attempting to identify factors that remove or attenuate interference. For example, it has been demonstrated that subjects can learn opposing force fields if the posture of the arm is altered between the two fields (Gandolfo et al, 1996) or if contextual cues are provided appropriately (Krouchev and Kalaska, 2003;Osu et al, 2004). …”
Section: Introductionmentioning
confidence: 99%